Kehidupan Kaum Minoritas Muslim Hui dan Uyghur di Negeri Tirai Bambu - Muh. Hanif; Amanatul Maula (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Being a minority is not an easy thing, it is also experienced by the people of the season. Muslims in China often experience discrimination, especially for Uyghur Muslim communities, Although Muslims in China are not only Uyghurs but the government often discriminates against Uyghurs, they are often referred to as Theorists because of their Turkish ancestors. This study of researchers wants to examine how the lives of minorities for Hui Muslims and Uyghurs live in the bamboo curtain country, as well as how the history of the entry of Islam in China and how they gained their identity. This type of research is qualitative research. The method used is a literature study taken from several journals as well as articles and videos on youtube. The purpose of this research is that the wider community can understand the related muslim life in China.